Two-color photometry with high temporal resolution of the extremely variable blazar PKS 0537-441 - Romero, Gustavo Esteban (2000)
We report the results of a microvariability monitoring campaign on the southern blazar PKS 0537-441. The source was observed in the V and R optical bands throughout six consecutive nights. Strong variations at both bands, with amplitudes of ∼0.3 mag, were observed on timescales of about 2 days. Smaller fluctuations of ∼0.05 mag on a scale of a couple of hours are superposed on the larger outburst. The spectral index was also variable during the observing period, with an average value of α = -1.6 and changes up to ∼27.5%. The spectrum varies in the sense that it becomes harder when the source is brighter, in accordance with predictions of shock-in-jet models. We discuss our results and the possible origin of the variability in this blazar in light of recent higher frequency observations.